Penggunaan Cadar di Kalangan Mahasiswi: Studi Tentang Makna, Motivasi, dan Diskriminasi - Soleman, Soleman; Khairan, Khairan; Syahputra, Nanda; Alfia, Reni Septri; Mahmani, Sri; Munawita, Munawita (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2023)
This article aims to describe the meanings, motivations, and discrimination related to the use of veils among students at UIN Ar-Raniry. This research utilizes a qualitative descriptive approach, and data were obtained from various sources, including field observations, direct interviews with informants, and relevant scholarly literature. The findings of this study indicate that female students interpret the use of veils in various ways, such as self-defense, an expression of obedience to God, and an understanding of Islamic law. They also view the veil as a means to protect themselves from unwanted attention, as part of their journey of religious conversion, and as a way to maintain modesty and behavior in accordance with Islamic teachings. Motivations behind the use of veils by female students include a desire to draw closer to Islamic teachings, self-protection, and social influence. This reflects a combination of psychological, social, and spiritual factors in their decision to wear the veil. This study also reveals that some female students experience discrimination and negative stereotypes as a result of wearing veils, including being perceived as extremists or terrorists. These experiences indicate that the use of veils in an academic environment can also trigger prejudice and negative social reactions. Abstrak Artikel ini bertujuan untuk mendeskripsikan makna, motivasi, dan diskriminasi terkait penggunaan cadar di UIN Ar-Raniry. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dan data diperoleh dari berbagai sumber, termasuk observasi lapangan, wawancara langsung dengan informan, dan literatur ilmiah yang relevan. Hasil kajian ini menunjukkan bahwa mahasiswi memaknai penggunaan cadar secara beragam seperti pertahanan diri, ekspresi ketaatan kepada Tuhan, dan pemahaman terhadap hukum Islam. Mereka juga melihat cadar sebagai cara untuk melindungi diri dari perhatian yang tidak diinginkan, sebagai bagian dari perjalanan hijrah mereka, dan sebagai sarana untuk menjaga kesopanan serta perilaku yang sesuai dengan ajaran Islam. Motivasi di balik pemakaian cadar oleh mahasiswi meliputi keinginan mendekatkan diri pada ajaran Islam, perlindungan diri, dan pengaruh sosial. Ini mencerminkan perpaduan faktor psikologis, sosial, dan spiritual dalam keputusan mereka untuk bercadar. Kajian ini juga menunjukkan bahwa beberapa mahasiswi juga mengalami diskriminasi dan stereotip negatif akibat pemakaian cadar, termasuk dianggap sebagai ekstremis atau teroris. Pengalaman tersebut mengindikasikan bahwa penggunaan cadar dilingkungan akademis juga dapat memicu prasangka dan reaksi sosial yang negatif.